Evaluation of the floral rewards of Aloe greatheadii var davyana (Asphodelaceae), the most important indigenous South African bee plant - Nicolson, Sue W. (University of Pretoria, 2013)
Thesis (PhD (Entomology))--University of Pretoria, 2008.